A review on persulfates activation by functional biochar for organic contaminants removal: Synthesis, characterizations, radical determination, and mechanism. Issue 5 (October 2021) - Wang, Chongqing; Huang, Rong; Sun, Ruirui; Yang, Jiapeng; Sillanpää, Mika
Abstract: In recent years, refractory organic pollutants (ROPs) have been progressively detected in wastewater. Persulfates (peroxymonosulfate and peroxydisulfate)-based advanced oxidation processes (PS-AOPs) are efficient for ROPs degradation. Biochar and its composites, which have the dual advantages of adsorption and catalysis, have been widely used in PS-AOPs. Research advances on PS activation by biochar-based materials are systematically summarized, including biochar modifications, characterizations, radical determinations, and catalytic mechanism. Biochar modifications applied to PS-AOPs are introduced involving morphology regulation, heteroatomic doping, and metals loading. Characterization techniques are described to reveal the physicochemical properties of biochar-based catalysts. Various methods for radical determinations are discussed. The catalytic mechanism in the PS-AOPs is depicted from the point of radical pathway and non-radical pathway. Based on current knowledge, the perspectives and challenges that may be encountered in basic research and practical applications are put forward. This review offers novel insights into catalyst design and better understanding of PS-AOPs. Graphical Abstract: ga1 Highlights: Persulfates-based advanced oxidation processes were reviewed to for ROPs removal. Heteroatomic doping and metals loading are promising to improve catalytic ability of biochar. Catalytic mechanism was discussed from radical pathway and non-radical pathway. The perspectives and challenges for biochar catalyzed PS-AOPs are proposed based on current knowledge.